The Textual Evolution of the Ottoman "Şeyhülislams' Fetvas": A Cross-Corpora Computational Analysis - Ergene, Boğaç A. (Der Islam, 2021)
In this article, we use a mix of computational techniques to identify textual shifts in the Ottoman şeyhülislams' fetva s between the sixteenth and twentieth centuries. Our analysis, supplemented by a close reading of these texts, indicates that the fetva s underwent multiple forms of transformation, a consequence of the institutional evolution of the şeyhülislam's fetva office (fetvahane) that aimed to speed up and streamline the production of the fetvas: over time, the texts appropriated a more uniform character and came to contain shorter responses. In the compositions of the questions, we identified many "trigger terms" that facilitated reflexive responses independent of the fetvas'jurisprudential contexts, a tendency that became stronger after the second half of the seventeenth century. In addition, we propose in the article a methodology that measures the relative strengths of textual and conceptual links among the fetva corpora of various Ottoman şeyhülislams. This analysis informs us about possible paths of long-term evolution of this genre of jurisprudential documents.